Evaluating the Effects of Flexible Learning about Aseptic Compounding on First-year Students in a Pharmacy Skills Laboratory - Neville, Michael W (Am J Pharm Educ, 2015)
Objective. To evaluate how flexible learning via online video review affects the ability and confidence of first-year (P1) pharmacy students to accurately compound aseptic preparations. Design. Customary instructions and assignments for aseptic compounding were provided to students, who were given unlimited access to 5 short review videos in addition to customary instruction. Student self-confidence was assessed online, and faculty members evaluated students’ aseptic technique at the conclusion of the semester. Assessment. No significant difference on final assessment scores was observed between those who viewed videos and those who did not. Student self-confidence scores increased significantly from baseline, but were not significantly higher for those who viewed videos than for those who did not. Conclusion. First-year students performed well on final aseptic compounding assessments, and those who viewed videos had a slight advantage. Student self-confidence improved over the semester regardless of whether or not students accessed review videos.